"Mene so potolažili s tem, da so mi zagotovili županstvo" - Gašparič, Jure (Studia Historica Slovenica, 2017)
In this piece the authors focus on the brief period in 1935 when the capital of the Drava banovina in the Kingdom of Yugoslavia was governed by the liberal politician and mayor Dr. Vladimir Ravnihar. Coming from the fact that this was a time of an undemocratic regime established by King Aleksander Karadđorđevič on the one hand, and the fact that this was a time when there were signs of political changes at the highest levels in Belgrade, they first focus on the international political circumstances that brought Ravnihar at the helm of the Ljubljana municipality. In the second part they present in a condensed manner Mayor Ravnihar, the particularities of his mandate as well as his fast and unusual end.
Keywords: Ljubljana; lokalna samouprava; politična zgodovina; Ravnihar, Vladimir; Slovenija; zgodovina